Optimal design of a two-point variables skip-lot sampling plan with Taguchi capability index. Issue Volume 35:Issues 1(2023) (2nd January 2023) - Wang, Zih-Huei
Abstract: The skip-lot sampling plan, an extension of the lot-by-lot based plan, not only retains the original characteristic of every lot inspection, but also skips lots appropriately when lot acceptance criterion is satisfied. Past studies have revealed that the skip-lot sampling plan saves more inspection samples than the traditional single sampling plan. However, most research related to the skip-lot sampling plan for variables lacks the additional loss assessment, when the quality deviated from the target value. Hence, this study proposes a skip-lot sampling plan based on the Taguchi capability index for variables products. The performance of the designed plan is investigated in terms of the operating characteristic curve and average sample number. Additionally, for the purpose of discussing how to select sampling frequency in this approach, a simulation study for average run length is conducted for validation. Finally, one practical case is presented for illustrating how to apply proposed method to resistor manufacturing to verify its applicability. Research Highlights: The core findings of the article are listed below: A new type of skip-lot sampling plan based on Cpm index is developed. A nonlinear optimization model is constructed for selecting the plan's parameters. The performance is investigated and compared with traditional plans. A simulation study provides a guideline for selecting sampling frequency in practice. One practical case is presented for illustrating the proposed plan's applicability.